Effectiveness of Media Hand Puppet Show to Grow Interest in Learning Students Learning at Kusala Sikkha Buddhist Sunday School - Mauludiyati, Sri; Setyaningsih, Setyaningsih (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2018)
The success of the students in education is influenced by the role of a supervisor who is able to direct the students on fun learning conditions. Children’s difficulties in understanding the subject matter are commonly found in learning activities. Teachers often use a lecturing method and rarely use media in teaching. The lack of use of the media in the process of learning makes learning less varied. One way to get children's attention to focus and engage their interest on the learning of Buddhism at the SMB is the use of tools or learning effective media, namely hand puppet show. This study aims to foster student interest Kusala Sikkha Buddhist Sunday School (BSS) Vihāra Dhamma Sukha Kenteng through the use of the hand puppet show media. This research is a classroom action research with 15 students as research subjects at primary school student in BSS Kusala Sikkha Vihāra Dhamma Sukha in Kenteng. The data were collected by questionnaire interest, observations, interviews, and documentation. The descriptive data were analyzed qualitatively through the stages of the cycle. The results showed that the use of hand puppet show media or a puppet show is very effective to foster the students’ interest. This was evident from the results of the study which showed an increase in the students’ interest in the first cycle to reach an average of 15.25, and the second cycle reached an average of 19. Thus, interest in students’ learning after the implementation of action rose up to 3.75. Increased interests were seen from four aspects, namely: (1) intention: the students were very enthusiastic and active in group discussions, students were happy and excited; (2) diligence and seriousness: the students were able to complete the story well and focused on thelearning activities; (3) concern: the students listened and appreciated the story themes from other groups; (4) attitude: the students dared to tell their friends spontaneously using hand puppets and were able to explain the story line well. The effectiveness of the hand puppet show media in increasing student interest in the first cycle was 76% and increased in the second cycle reached 95%. The above description shows that the media hand puppet show can increase student interest BSS Kusala Sikkha.